Bạn chưa đăng nhập. Vui lòng đăng nhập để hỏi bài
Phạm Khánh Vi

giải phương trình \(\sqrt{x^2-6x+9}-2\sqrt{x-3}=0\)

Mai Vương Minh
6 tháng 11 2022 lúc 18:38

đkxđ

pt <=>\(\sqrt{\left(x-3\right)^2}-2\sqrt{x-3}=0\)

<=>\(\sqrt{x-3}\left(\sqrt{x-3}-2\right)\) =0

=>\(\left\{{}\begin{matrix}\sqrt{x-3}=0\\\sqrt{x-3}-2=0\end{matrix}\right.\)

<=>\(\left\{{}\begin{matrix}x=3\\x-3=4\end{matrix}\right.\)=>\(\left\{{}\begin{matrix}x=3\\x=7\end{matrix}\right.\)

 

 

Mai Vương Minh
6 tháng 11 2022 lúc 18:38

ĐKXĐ: \(x\ge3\)


Các câu hỏi tương tự
thiyy
Xem chi tiết
Trí Phạm
Xem chi tiết
6.Phạm Minh Châu
Xem chi tiết
Nguyễn Thị Ngọc Mai
Xem chi tiết
Nguyễn Thảo My
Xem chi tiết
Chau Pham
Xem chi tiết
Nguyen Ngoc Ha
Xem chi tiết
Đạm Đoàn
Xem chi tiết
Hoàng Thiên Băng
Xem chi tiết
Hoàng Vũ Lê
Xem chi tiết